Profiling Transcriptional Response of Dengue-2 Virus Infection in Midgut Tissue of Aedes aegypti - Chen, Tse-Yu; Lee, Yoosook; Wang, Xiaodi; Mathias, Derrick; Caragata, Eric P.; Smartt, Chelsea T. (Frontiers in Tropical Diseases, 2021)
Understanding the mosquito antiviral response could reveal target pathways or genes of interest that could form the basis of new disease control applications. However, there is a paucity of data in the current literature in understanding antiviral response during the replication period. To illuminate the gene expression patterns in the replication stage, we collected gene expression data at 2.5 days after Dengue-2 virus (DENV-2) infection. We sequenced the whole transcriptome of the midgut tissue and compared gene expression levels between the control and virus-infected group. We identified 31 differentially expressed genes. Based on their function, we identified that those genes fell into two major functional categories - (1) nucleic acid/protein process and (2) immunity/oxidative stress response. Our study has identified candidate genes that can be followed up for gene overexpression/inhibition experiments to examine if the perturbed gene interaction may impact the mosquito’s immune response against DENV. This is an important step to understanding how mosquitoes eliminate the virus and provides an important foundation for further research in developing novel dengue control strategies.